New Generation of Counter UAS Systems to Defeat of Low Slow and Small (LSS) Air Threats - Dominicus, J.W. (NATO, 2021)
Detecting, classifying, identifying, tracking and defeating low, slow and small air threats presents a major challenge for existing sensor and effector systems. So-called first generation C-UAS systems often rely on detecting the datalink from the controller to the drone which provides limited capability against current threats. However, this means of detecting drones is a challenge when operators manipulate standard datalinks and will not work at all against current and future autonomous drones. Other current methods of detecting and neutralising drones include for example combining radar with optical sensors. These systems are not always reliable, can generate large numbers of false alerts and are often manpower intensive to operate. The NATO SCI-301 Research Task Group (RTG) has been working on specifying what second generation C-UAS systems should entail. The paper will outline the findings of this RTG over the past three years.